Financial inclusion, regulation, financial literacy, and financial education in Tajikistan - Roman Mogilevskii; Shokhboz Asadov (Asian Development Bank Institute (ADBI), 2018)
This paper provides an analysis of financial inclusion, literacy, and education issues in the Republic of Tajikistan. It discusses the recent progress in financial inclusion and the sector's response to the major external shock associated with the sharp fall in Tajik labor migrants' remittances. The policies dealing with different aspects of financial inclusion are analyzed with a focus on the regulatory framework, penetration of new financial technologies, and the existing barriers to inclusion. The paper provides a set of recommendations for improving the situation with financial inclusion and financial literacy in the country.
Keywords: G21; G28; O16; 330; financial inclusion; financial literacy and education; Tajikistan